The Principal of the Theory of Morphosyntax in the Kurdish Language under the Light of Generative Grammar (Raparin Journal of Humanities (RJH), 2025)
This research, entitled “The Principal of the Theory of Morphosyntax in the Kurdish Language under the Light of Generative Grammar”, is an attempt to clarify morphosyntax in a way that differs from previous studies and to present this new linguistic level in a different format, Since the exact details and significance of morphosyntax in Kurdish language are still unknown, For this reason, we examined the function, impact, and modifications that morphosyntax makes to language, This study also provides a thorough answer to the question “What is morphosyntax?” and establishes the theoretical foundations necessary for explaining morphosyntactic structures, In addition, presenting "The Theory of Morphosyntax" in the context of the Kurdish language is a subject that has not yet been properly examined by earlier researchers, which is another innovative aspect of this study, Furthermore, we discussed the unique features of morphosyntax and its structural elements, emphasising the structural elements in the Kurdish language, and we explained it with examples, One of the key linguistic theories referenced in this study is Chomsky’s generative grammar, through which we have made this linguistic level in the form of generative syntax, A new stage in the development of grammar emerged, giving rise to the theory of authority and association, which in turn led to the formation of morphosyntax interfaces and the analysis of examples, This theoretical technique has been used to evaluate and analyse a number of examples. We are now done exploring the differences between morphosyntactic and syntactic structures and their dynamic interaction.